The Impact of Cultural Values on Job Satisfaction and Organizational Commitment in Self-Managing Work Teams: The Mediating Role of Employee Resistance - Kirkman, Bradley L.; Shapiro, Debra L. (Academy of Management Journal, 2001)
Using a field survey of 461 self-managing work team members in four countries, we examined: (1) whether employee resistance to such teams mediated the relationships between employee cultural values and job attitudes and (2) whether the value-resistance relationships were stronger in some countries than in others. Results show that resistance mediated the cultural value-job attitude relationships, sometimes fully and sometimes partially, depending on which type of resistance (to teams or to self-management) and which type of cultural value was being examined. Theoretical and practical implications are discussed.